Putin’s 2020 State-of-the-Nation Address : More Power? - Cheang, Chris (2020)
Unlike the last two years, Putin’s latest State-of-the-Nation address focussed more on domestic socio-economic issues, in particular the future of the presidential system of government. The absence of criticism of the West signals Russia’s willingness to normalise ties with it.